Morphological and functional outcome of N- butyl cyanoacrylate tissue adhesive application in corneal perforations - Raj, Anuradha; Dhasmana, Renu; Bahadur, Harsh (Nepalese Journal of Ophthalmology, 2020)
Introduction: This study was conducted to characterize morphological and functional outcome of application of tissue adhesive (TA) in corneal perforations. Methods: This is a retrospective study in which data of corneal perforations which were managed by application of TA (N- butyl cyanoacrylate) from January 2015 to April 2018 were reviewed. The final outcome of TA in corneal perforation was considered as sealed or non-sealed over a period of three months. Criteria of success of TA application included resolution of infiltrates, corneal vascularisation and scarring. Morphological outcome was considered as corneal scarring, required therapeutic penetrating keratoplasty (TPK) and loss of anatomical integrity of globe as phthisis bulbi. Functional success was considered preservation of visual function with best corrected visual acuity (BCVA). Results: A total of sixty seven eyes of sixty seven patients were reviewed in the present study. The mean age of all the patients was 46.63 ±16.30 years (range: 5-81 years) with predominance of males 41(61.19%). Infective keratitis (IK) constituted major chunk of aetiology for corneal perforations 44(65.67%) with maximum 47(70.14%) of size of ≥1.5-3.0mm. 56(83.58%) cases sealed completely, rest 11(16.41%) cases failed to seal. Morphological outcome showed significant relationship with age, number of glue applications and complications with P value (0.05, 0.00, 0.00) respectively. The functional outcome showed significant relationship with age, frequency of applications, morphological outcome and complications (p value 0.02, 0.00, 0.00, 0.00) respectively. Conclusions: Infective keratitis is major cause of corneal perforations. Corneal perforations ≤3.0mm size shows healing and subsequent closure in 83.58%. Morphological and functional outcome shows significant relationship with age, number of glue applications and complications.